Comparative study between Harmonic FOCUSTM to clamp and tie technique for total thyroidectomy - Saloom, Adil K.; AbdulJabbar, Mohammed Q. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Thyroid surgery has undergone many changes during the past 2 decades, including the introduction of new surgical techniques such as endoscopic or video-assisted approaches, anesthesia care, intraoperative nerve monitoring and new hemostatic toolsObjectives: to assess the efficacy and safety of Harmonic Focus shears in total thyroidectomy compared with conventional surgical technique.Patients and methods: prospective study conducted from October 2011 till January 2016, two handers and nine patients with benign and malignant thyroid diseases, scheduled for total thyroidectomy in a governor and private hospitals were enrolled randomly into 2 groups, group A consists of 105 patient who undergone a total thyroidectomy using a harmonic FOCUSTM , and group B consists of 104 patients who underwent total thyroidectomy with conventional surgical technique.Results: Eleven patients had papillary thyroid carcinoma: 6 (5.7%) of them in group A and 5(4.8%) in group B. Eighty seven (82.9%) patients in group A had non toxic MNG, and 12(11.4%) patients had toxic MNG, 90 (86.5%) patients in group B had non toxic MNG while the other 9 (8.7%) had toxic MNG. Mean operative time was significantly lower in group A compared to Group B (100+/- 34 vs. 119+/- 30mins, respectively). In group A mean calcium level at first post-operative day was 8.36 +/- 0.54 mg/dl. In group B mean value was 8.12+/- 0.56 mg/dl. This difference was not statistically significant. There were no significant difference between the two groups concerning transient hypocalcemia requiring calcium and Vitamin D therapy: 11(10.5%) patients in group A versus 12(11.5%) in group B. No permanent hypocalcemia was found in both groups. Two patients had transient vocal cord palsy in group A(1.9%) versus 3 patients in group B (2.8%)Conclusions: The HF is a reliable, comfortable and safe instrument alternative to knot tying technique, very suitable hand-piece for total thyroidectomy. It creates a clean, bloodless surgical field, and there is an advantage for the surgeon to use a single tool for both dissection and hemostasis. Moreover, the HF is a time-saving option, allowing for a significant reduction of operative time, without affecting parathyroid function, need for medical therapy, and hemostasis in the early post-operative period.